Answer:
D = 90°
Step-by-step explanation:
the square on the angle means its a right angle and right angle is always 90°
There are web sites and videos that stand ready to show you how to bisect an angle.
The basic idea is that you draw an arc through both rays so that the points of intersection are the same distance from the vertex. Then, you construct a perpendicular bisector of the segment between those intersection points. That will bisect the angle.
For (3), you bisect each of the angles made by the original bisector. (1/2 of 1/2 = 1/4)
Answer:
x + y = 330 and 9x + 16y = 4650
Step-by-step explanation:
At a museum, the admission price for children is $9 and the admission price for adults is $18. The total amount the museum collects in admissions for the day is $4959. The total number of visitors is 319.
x = number of children
y = number of adults
x + y = 330
9x + 16y = 4650
Answer:
![x=-4](https://tex.z-dn.net/?f=x%3D-4)
![y=3](https://tex.z-dn.net/?f=y%3D3)
![z=-5](https://tex.z-dn.net/?f=z%3D-5)
Step-by-step explanation:
<u>Given:</u>
![x+y+z=-6](https://tex.z-dn.net/?f=x%2By%2Bz%3D-6)
![x-6y-7z=-29](https://tex.z-dn.net/?f=x-6y-7z%3D-29)
![-7y-5z=4](https://tex.z-dn.net/?f=-7y-5z%3D4)
<u>Solve for </u>
<u> in the 1st equation:</u>
![x+y+z=-6](https://tex.z-dn.net/?f=x%2By%2Bz%3D-6)
![x+y=-z-6](https://tex.z-dn.net/?f=x%2By%3D-z-6)
![x=-y-z-6](https://tex.z-dn.net/?f=x%3D-y-z-6)
<u>Substitute the value of </u>
<u> into the 2nd equation and solve for </u>
<u>:</u>
![x-6y-7z=-29](https://tex.z-dn.net/?f=x-6y-7z%3D-29)
![(-y-z-6)-6y-7=-29](https://tex.z-dn.net/?f=%28-y-z-6%29-6y-7%3D-29)
![-7y-z-13=-29](https://tex.z-dn.net/?f=-7y-z-13%3D-29)
![-7y-z=-16](https://tex.z-dn.net/?f=-7y-z%3D-16)
![-z=-16+7y](https://tex.z-dn.net/?f=-z%3D-16%2B7y)
![z=16-7y](https://tex.z-dn.net/?f=z%3D16-7y)
<u>Substitute the value of </u>
<u> into the 3rd equation and solve for </u>
<u>:</u>
![-7y-5z=4](https://tex.z-dn.net/?f=-7y-5z%3D4)
![-7y-5(16-7y)=4](https://tex.z-dn.net/?f=-7y-5%2816-7y%29%3D4)
![-7y-80+35y=4](https://tex.z-dn.net/?f=-7y-80%2B35y%3D4)
![28y-80=4](https://tex.z-dn.net/?f=28y-80%3D4)
![28y=84](https://tex.z-dn.net/?f=28y%3D84)
![y=3](https://tex.z-dn.net/?f=y%3D3)
<u>Plug </u>
<u> into the solved expression for </u>
<u> and evaluate to solve for </u>
<u>:</u>
![z=16-7(3)](https://tex.z-dn.net/?f=z%3D16-7%283%29)
![z=16-21](https://tex.z-dn.net/?f=z%3D16-21)
![z=-5](https://tex.z-dn.net/?f=z%3D-5)
<u>Plug </u>
<u> into the solved expression for </u>
<u> and evaluate to solve for </u>
<u>:</u>
![x=-(3)-(-5)-6](https://tex.z-dn.net/?f=x%3D-%283%29-%28-5%29-6)
![x=-3+5-6](https://tex.z-dn.net/?f=x%3D-3%2B5-6)
![x=2-6](https://tex.z-dn.net/?f=x%3D2-6)
![x=-4](https://tex.z-dn.net/?f=x%3D-4)
Therefore:
![x=-4](https://tex.z-dn.net/?f=x%3D-4)
![y=3](https://tex.z-dn.net/?f=y%3D3)
![z=-5](https://tex.z-dn.net/?f=z%3D-5)
Answer:
hope this helped you
please mark as the brainliest (ㆁωㆁ)